HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA REMAJA DI PERUMAHAN PURI PERMAI TIGARAKSA MASA PANDEMI (COVID-19) - Indri Damayanti. R; Eva Marsepa; Ayu Pratiwi (Nusantara Hasana Journal, 2022)
Teenagers are often tired during the day because they go to bed late and wake up early for school. Ideal night's sleep of 8-10 hours. Objective to find out whether there is a relationship between the use of social media and sleep quality in adolescents in Puri Permai Tigaraksa Housing during the pandemic (Covid-19). Research design is descriptive correlation. And quantitative this design is used to determine the relationship between social media use and sleep quality. Sampling in this study used the Probability Sampling method with the accidental sampling technique, the number of respondents was 55 people. Data analysis using Chi Square data test. Results univariate that Gender, and Age and Bivariate using Chi Square Social Media results from 55 respondents obtained Good results totaling 44 (82.5%) respondents and Bad results totaling 11 (17,5%), Respondents and sleep quality from 55 respondents obtained Good results amounting to 42 (80.0%), and for respondents obtained Bad results totaling 13 (20.0%) Respondents the relationship between social media use and sleep quality in Teenagers in the Puri Permai Tigaraksa Housing during the (Covid -19) pandemic had a P-Value 0.07, then Ho wich means that there is no relationship between socia; media use and sleep quality. There is a relationship between the use of social media with sleep quality.